Oldest co-occurrence of Varanus and Python from Africa—first record of squamates from the early Miocene of Moghra Formation, Western Desert, Egypt - Georgios L. Georgalis; Mohamed K. Abdel Gawad; Safiya M. Hassan; Ahmed N. El-Barkooky; Mohamed A. Hamdan (PeerJ, 2020)
Lizard and snake remains from the early Miocene (Burdigalian) of the Moghra Formation, Egypt, are described herein. This material comprises the first fossil remains of squamates recovered from the otherwise rich and well known vertebrate assemblage of Moghra. The material pertains to two different genera, the varanid lizard Varanus and the pythonid snake Python and adds to the so far rather poorly known squamate fossil record from Africa. On the basis of the new remains, Moghra marks the oldest so far described co-occurrence of Varanus and Python in the African continent. The close sympatry of these two genera in the African fossil record is thoroughly analyzed and discussed, a co-existence, which is still widespread in the extant herpetofauna of the continent. Situated rather close to the so called “Levantine Corridor” and dated at the Burdigalian, practically when Afro-Arabia collided with Eurasia, the Moghra squamate assemblage offers the potential of important insights in the biogeography and dispersal events of vertebrate groups during the early Miocene.